RASIONALITAS PENAFSIRAN IBNU ATHIYYAH - Karim, Abdullah (Jurnal Ilmiah Ilmu Ushuluddin, 2013)
Borrowing the definition used by Binyamin Abrahamov for discussion of theology: Rationality is treating any issues by using reason, but whitout giving priority reason. Thus, if it is associated with the interpretation means interpreting the Qur'an by using reasoning or ijtihad, but without making it as the main point. The use of reason in addition to a history that is valid in the interpretation of the Qur'an is a necessity. This is caused by the editors who sometimes use the Qur'an itself ambiguous pronunciation (musytarak / ambiguous) meaning there is even the opposite, or use a word with a specific meaning. However, the interpretation of rationality is limited in scope to understand the meaning or spelling or sentence structure verses (read: the discourse of) the Qur'an. Not including the use of analogy in legal dig no texts or texts in the Qur'an.